Continue keeping the united, unified in the Party follow Ho Chi Minh thought - Nguyễn Quang Bình (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The article focuses on clarifying the content of Ho Chi Minh’s thought on preserving unity and unity in the Party. This is one of the leading principles in the organization and operation of the Party. On the basis of a general assessment of the current situation, the author proposes a number of key measures to maintain and strengthen the unity and unity in the Party to meet the requirements and tasks of the new situation.